The Efficiency Of A Suggested Counseling Program For Relaxation Skill To Cope With Gymnasts’ Psychological Stress - Dissi Yahia Elhabib, Redouane (sports creativity, 2025)
The present study aims to identify the effects of a suggested counseling program for relaxation skill to cope with gymnasts’ psychological stress, through its application on a sample of 28 gymnasts suffering from psychological stress andrecording a high stress level in Sports Competition Anxiety Test (SCAT) (of Martens et al), which has been arbitrated by professionals. The method used in this study is experimental in which a control sample of 14 players, and an experimental one of 14 other players have been chosen to apply the counseling program for relaxation skill only on the experimental sample. After statistical process, statistically significant differences between the control and experimental sample groups have been noticed in favor of the experimental group, by considering the homogeneity of the sample members in the experimental and control groups in terms of variables of age, sex, athletic level, sports field, and the level of psychological stress before applying the suggested counseling program. After collecting, statistically processing, exposing, analyzing, and discussing data in the basis of a theoretical background and available previous or similar studies, the present study has found out that the suggested counseling program for relaxation skill leads to coping with gymnasts’ psychological stress